The effect of the platelet-rich plasma and ozone therapy on tendon-to-bone healing in the rabbit rotator cuff repair model - Gurger, Murat; Once, Gokhan; Yilmaz, Erhan; Demir, Sukru; Calik, Ilknur; Say, Yakup; Bingollu, Onur (Bmc, 2021)
BackgroundThe aim of this study is to histologically and biomechanically investigate the effects of local PRP and ozone therapy (O2O3) on tendon-to-bone healing in a rabbit model of the supraspinatus tendon tear.MethodsFour groups were formed to have seven rabbits in each group: repair, R; repair + PRP, RP; repair + ozone, RO; and repair + PRP + ozone, RPO. The supraspinatus tendon was detached by sharp dissection from the footprint and an acute tear pattern was created. Thereafter, tendon repair was performed with the transosseous technique. In the RP group, PRP, and in the RPO group, PRP + O2O3 mixture was injected to the tendon repair site. In the RO group, O2O3 gas mixture was injected into subacromial space three times a week for a total of 4 weeks. The study was ended at postoperative 6th week.ResultsWhen compared with the R group, a statistically significant increase was observed in the biomechanical strength of the RP and RPO groups. The highest increase in biomechanical strength was detected in the RPO group. The histology of the RO and RPO groups showed better collagen fiber continuity and orientation than the R and RP groups.ConclusionsThe results obtained from this study show that the ozonized PRP can be used as biological support to increase tendon-to-bone healing. However, these results need to be supported by clinical studies.
Keywords: Platelet-rich plasma; Ozone therapy; Tendon-to-bone healing; Rotator cuff